Particularités de la latinité roumaine. Relecture des recherches dans le domaine - Cosmin CĂPRIOARĂ (Diversitate si Identitate Culturala in Europa)
PARTICULARITIES OF ROMANIAN LATINITY. REVIEW OF RESEARCH IN THE FIELD This contribution presents an updated synthesis of research on the specificity of the Romanian language between all Romance languages. Our study deals with the peculiarities of Romanian which arise, mainly, as a result of certain tendencies manifested in Danubian Latin during the centuries which open the first millennium and of internal tendencies or external influences of the following period. Many of them represent further developments. Research on the individuality of the Romanian language in the Romania’ space accompanies the evolution of diachronic and synchronic comparative linguistics and other related disciplines. They belong in particular to Romanian scholars, including S. Puşcariu, I. Iordan, Al. Rosetti, Al. Niculescu, E. Coşeriu and others. The Romanian peculiarities concern all the compartments of the language: from phonetics and morphosyntax, including the order of words, to lexic and semantics. The proposed re-reading highlights how the concept of 'specificity' of the Romanian language has been shaped and reshaped based on the discoveries made by Romance linguistics during its development.